Chromophoric Dissolved Organic Matter and Dissolved Organic Carbon in Lakes Across an Elevational Gradient From the Mountains to the Sea - Kyle Juetten; Angela L. Strecker; Aaron Harrison; Zachary Landram; Warren J. DeBruyn; Catherine D. Clark (Earth and Space Science, 2022)
Abstract Dissolved organic matter (DOM) in lakes across elevation gradients is a complex function of topography, climate, vegetation coverage, land use, and lake properties. To examine sources and processing of DOM from sea level to mountain lakes (3–1,574 m), we measured dissolved organic carbon (DOC) concentrations and chromophoric dissolved organic matter (CDOM) optical properties, lake characteristics, and water quality parameters in 62 freshwater lakes in the Pacific Northwest, USA. Higher elevation lakes had lower DOC concentrations and absorbance. These lakes had higher forest cover and minimal wetlands in their watershed, in addition to low nutrients, water temperatures, and chlorophyll a in the lake itself. Two humic‐like and one protein‐like fluorescent component were identified from excitation‐emission matrix spectroscopy. The index of recent autochthonous contribution (BIX), fluorescence index (FIX), and SR optical indices showed that most lakes were dominated by terrestrially derived material. The humification index (HIX) and specific ultra‐violet absorbance (SUVA254) were consistent with more aromatic humic CDOM at lower elevations. The lower fluorescence of humic‐like components at higher elevation was attributed to lower inputs from vegetation. The relative contribution of the protein‐like component increased at higher elevation. This may be due to reduced allochthonous terrestrial inputs relative to in situ production of autochthonous material or increased photochemical/biological degradation of allochthonous material. Differences in optical characteristics associated with the amount and source of CDOM were observed across the elevational gradient. These differences were driven by characteristics at both within‐lake and watershed scales.